A Price is a signal: on intrinsic motivation and crowding-out - Friedel Bolle (European University Viadrina, Department of Business Administration and Economics, 2007)
If a previously unpaid activity (donating blood) is paid then we often observe that this activity is reduced. In this paper, it is hypothesised that the price offered is taken as a proxy for the "market value" of the activity. Depending on how the actor valued the activity previously, crowding-out or crowding-in, as well as persistence (or not) of the effect after the abandoning of payment is implied. This "naive" explanation is confronted with Bénabou and Tiroles (2003) priciple-agent model where the opposite signalling effect is hypothesised: a higher price is taken as an indication for a lower value.
Keywords: H42; D64; D82; 330; Intrinsic Motivation; Crowding-out; Signaling; Preis; Signalling; Motivation; Crowding out; Altruismus; Blutspende; Theorie